John Kennedy and His Interior policy in Untied States of America 1961 – 1963 (Journal of the College of Basic Education, 2023)
John Kennedy is considered as a prominent sign in the history of United Stated of America. Through sixtieth of the twenty century, His policy (limit by limit) had leaded to introduce a original changes on interior and exterior polies. The interior was oriented to the youth in which he had seen hope and future, the future which make U.S.A at the first class of labor countries. Such policy was different of the previous presidents by the approach of the managerial and political work. Therefore, his policy through his rule (1961- 1963) made effects in all fields of the society specially programs of development and social reform. He tried to accelerate the economic growth movement, increasing industrial investments, struggled in civil rights in order to ensure the rights of American black people, following women issues and recovering the equality movement with men. In education, he sought to develop education technology in all schools and colleges and attracts the nation to education compulsion. He issued codes the most important are the code of civil rights, health care and age care, the code of the great society to develop substructures of U.S.A. However, in 22 nov.1963 he was assassinated and he couldn’t see his results which are agreed and applied through the subsequent president Lyndon Johnson .